Student Teachers ’ Experiences of Mentorship during Teaching Practice in Tanzania - Mlyakado, Budeba Petro; Mwandambo, Ikupa Moses (Papers in Education and Development, 2024)
This study explores student teachers ' mentorship experiences during teaching practice in Tanzania. The study employed a case study design and collected data from 22 student teachers using focus group discussions. Data are analysed thematically. Results indicate that all sampled student teachers were attached to teacher-mentors, and the majority received support and mentorship. The mentorship received improved student teachers ' tolerance, confidence, and flexibility in the actual teaching environment. Nevertheless, some student teachers received superficial or no mentorship because teacher-mentors were absent or uninterested in doing so. Few student teachers reported being overwhelmed by the teaching workload. These findings are discussed, and suggestions for improvement are offered. Keywords: Mentorship, student teachers, teacher-mentors, teaching practice, Tanzania